Psycho-motor analysis of athletes under overtraining stress - Maman, P.; Khanna, N.; Sandu, J. S. (Serbian Journal of Sports Sciences, 2012)
The purpose of the present study was to compare and investigate the relation between the scores in the Training Stress Scale, Reboundability Subscale and Psychomotor Performance as assessed by the Motor Performance Series in the Vienna Test System. The total of 100 athletes (65 males, 35 females) from various sports was divided into three stress groups: High Stress Group (HSG), Moderate Stress Group (MSG), and Low Stress Group (LSG) according to the Training Stress Scale scores. One-way ANOVA indicated a significant difference among the three groups for the Training Stress Scale